Development of English Skills for Manpower in Thai Film Industry on Metaverse - Piayura, Orathai; Boonmas, Thidarat; Wongphongkham, Niyom; Sae-joo, Phongthanat; Narongchai, Wanichcha; Wongphongkham, Hava; Promphakping, Buapun (ECT Education and Communication Technology Journal, 2025)
The objectives of this research were: 1) to study English skills of the workforce in the Thai film industry in virtual spaces, 2) to develop a platform for enhancing English skills in virtual spaces, and 3) to propose guidelines for driving the development of English skills for the workforce in the Thai film industry in virtual spaces. The samples included: 1) students in fields related to the film industry, 2) operational personnel in the film industry, and 3) government officials and personnel in the film industry chain. The sample comprised 82 people selected through purposive sampling. The research instruments were: 1) opinion interview forms and 2) platform quality assessment forms. Data were analyzed using mean, standard deviation, and content synthesis analysis. The research findings were as follows: 1) The study found that from the workforce perspective, factors including politics, economics, society, technology, environment, law, skills, personnel, shared values, and networks with foreign companies can contribute to the development of the Thai film industry on the world stage. 2) The platform development results showed that the overall quality of the platform for developing English skills in virtual spaces in terms of functionality was at a very good level (M = 4.25, SD = 0.58). 3) The findings on guidelines for driving English skill development revealed that students and personnel need to improve their English skills, with emphasis on speaking and communication skills, specialized vocabulary, and virtual film classroom simulations.